Novel fully digital workflow for removable partial denture fabrication: Alur kerja digital lengkap terbaru dalam pembuatan gigi tiruan sebagian lepasan - Eri Hendra Jubhari; Priscilia Yoviani Sole (Makassar Dental Journal, 2022)
Background: Digital dentistry technology based on computer-aided design and computer-aided manufacturing (CAD/CAM) has been widely applied in the field of prosthodontics, ranging from digital techniques for impression processes, jaw registration, artificial tooth arrangement and base design, along with base and denture fabrication. However, conventional analog workflows are still used and digital workflows have not completely replaced analog workflows. Purpose: Knowing the latest complete digi-tal workflow in the manufacture of removable partial dentures (RPD). Methods: Full-arch digital impressions of the partially edentulous jaw were made with an intraoral scanner or by conventional methods. The denture framework, artificial teeth, and denture base were designed by commercially available CAD software. Each of the denture components including connectors, clasps, and artificial teeth and the denture bases were fabricated separately by the CAM machine, and then assembled using an adhesive material. Conclusion: RPDs were successfully fabricated using a fully digital workflow and no clinical complications were reported.